Advancements in sorption-enhanced steam reforming for clean hydrogen production: a comprehensive review - Farooqi, Ahmad Salam; Allam, Abdelwahab N.; Shahid, Muhammad Zubair; Aqil, Anas; Fajri, Kevin; Park, Sunhwa; Abdelaziz, Omar Y.; Abdelnaby, Mahmoud M.; Hossain, Mohammad Mozahar; Habib, Mohamed A.; Hasnain, Syed Muhammad Wajahat ul; Nabavi, Seyed Ali; et al. (Elsevier, 2025)
The sorption-enhanced steam methane reforming (SE-SMR) process, which integrates methane steam reforming with in situ CO2 capture, represents a breakthrough technology for clean hydrogen production. This comprehensive review thoroughly explores the SE-SMR process, highlighting its ability to efficiently combine carbon capture with hydrogen generation. The review evaluates the mechanisms of SE-SMR and evaluates a range of innovative sorbent materials, such as CaO-based, alkali-ceramic, hydrotalcite, and waste-derived sorbents. The role of catalysts in enhancing hydrogen production within SE-SMR processes is also discussed, with a focus on bi-functional materials. In addition to examining reaction kinetics and advanced process configurations, this review touches on the techno-economic aspects of SE-SMR. While the analysis does not provide an in-depth economic evaluation, key factors such as potential capital costs (CAPEX), operational expenses (OPEX), and scalability are considered. The review outlines the potential of SE-SMR to offer more efficient hydrogen production, with the added benefit of in situ carbon capture simplifying the process design. Although a detailed economic comparison with other hydrogen production technologies was not the focus, this review emphasizes SE-SMR's promise as a scalable and flexible solution for clean energy. With its integrated design, SE-SMR offers pathways to industrial-scale hydrogen production. This review serves as a valuable resource for researchers, policymakers, and industry experts committed to advancing sustainable and efficient hydrogen production technologies.
Keywords: Clean hydrogen; Carbon capture and storage (CCS); Sorption-enhanced steam methane reforming (SE-SMR); Sustainable energy production; Solid sorbents; 4004 Chemical Engineering; 40 Engineering; 7 Affordable and Clean Energy; 12 Responsible Consumption and Production; 13 Climate Action